The Disruptive Innovation of Communicative Language Teaching (CLT) in English Language Presentations for Economic and Management Knowledge - Hengki Hengki; Ratna Ratna; Nina Anis (Journal Emerging Technologies in Education, 2025)
Background. This paper aims to provide an overview of the key findings and implications of the research conducted. The present study examines the impact of communicative language teaching (CLT) as a disruptive innovation on the pedagogy of English language instruction. Purpose. This paper aims to provide an overview of the key findings and implications of the research conducted. The present study examines the impact of communicative language teaching (CLT) as a disruptive innovation on the pedagogy of English language instruction for the acquisition of knowledge in the fields of management and economics. Method. The implementation of the Critical Learning Theory (CLT) presents a novel pedagogical strategy that fosters the development of critical thinking abilities, enhances effective communication skills, and cultivates cultural competency. Results. This essay examines the fundamental principles of Communicative Language Teaching (CLT) and its integration into the domains of economics and management education. Additionally, it investigates the impact of CLT on both educators and learners. Conclusion. Based on the findings, the incorporation of CLT has the potential to enhance students' competence and engagement, thereby equipping them with the necessary skills to thrive in the competitive.